Making of international law - Boyle, Alan E.; Chinkin, C. M. (Oxford ; New York : Oxford University Press, 2007)
Studying the principal negotiating processes and law-making tools by which international law is developed, this book looks at the UN, diplomatic conferences, codification bodies, NGOs, and courts in identifying the processes, participants and instruments used in the making of international law.
International law-making -- Participants in international law-making -- Multilateral law-making: diplomatic processes -- Codification and progressive development of international law -- Law-making instruments -- Law-making by international courts and tribunals.
Includes bibliographical references (pages 313-329) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: International law; International agencies; International courts; Treaties; International agencies; International courts; International law; Treaties